Pengumuman Pemberlakuan PPKM Jawa-Bali Terhadap Saham-Saham Jakarta Islamic Index (JII) di Bursa Efek Indonesia - Listyaningsih, Erna; Luthfi, Muhammad (Universitas Malahayati, 2021)
Due to an increase in cases of the Corona virus spreading in Indonesia in 2021, the Indonesian government published a policy on July 3-20, 2021 to adopt the Implementation of Community Activity Restrictions (PPKM) for Java-Bali to break the chain of the Corona virus spreading. The goal of this research is to see how the JII stock reacts to the PPKM announcement. The event study methodology is applied to a sample of 30 JII. The findings of this study revealed that considerable anomalous returns occurred on the 2nd and 5th days after the event day, as well as on the 6th, 7th, 9th, and 10th days prior to the event date. Similarly, before and after the announcement of PPKM in Indonesia, TVA reveals a considerable variation. This demonstrates that there is a JII response to this event. The regression test, on the other hand, shows that the market has no effect on JII's return or TVA. This suggests that investors have anticipated this event, ensuring that there would be no excessive investor transactions